HAZARD ZONING FOR BALLISTIC IMPACT DURING VOLCANIC EXPLOSIONS AT VOLCÁN DE FUEGO DE COLIMA (MÉXICO) - Alatorre-Ibargüengoitia M.A.; Delgado-Granados H.; Farraz-Montes I.A. (My University, 2006)
Volcanic explosions expel fragments following ballistic trajectories. The volcanic ballistic projectiles represent a hazard due to their high velocities and temperatures. They may affect people, ecology, infrastructure, and aircraft. In order to avoid volcanic ballistic projectile-related hazards, a map can be constructed. A volcanic ballistic projectiles hazard map depicts the likely distribution and maximum range of ballistic projectiles under given explosive scenarios. Different level hazard zones shown on the map allow local inhabitants and concerned authorities to make development, protection, and mitigation plans, and to define restricted areas. In order to determine the potential areas where the ballistics may fall, it is necessary to estimate their maximum range under different explosive scenarios. Explosive magnitude scenarios are defined by their characteristic kinetic energy. Therefore, the ballistic projectiles reach maximum distance from the source according to the maximum energy for each scenario. The trajectories described for the ballistic projectiles are determined by gravity and drag forces. Drag force depends, among other factors, on the drag coefficient (a function of the geometry of the ballistics). The maximum range of the projectiles depends also on the initial kinetic energy, the "launching" angle, the ballistic diameter, and the wind velocity. Another relevant aspect is that drag force is proportional to the air density (which decreases with altitude), and so projectiles with a given velocity (or kinetic energy) reach larger distances and heights at volcanoes with higher altitudes. This fact is important in the case of Volcán de Fuego de Colima (México) where the crater altitude is 3860 m above sea level. This work presents a useful hazards map for Volcán de Fuego de Colima based on ballistic data from this and other volcanoes. © 2006 Geological Society of America.
Keywords: BALLISTIC PROJECTILES; COLIMA VOLCANO; HAZARDS MAPS; MÉXICO; VOLCANIC EXPLOSIONS